Avaliação de parâmetros de corte no microfresamento da liga Inconel 718 - Souza, Arthur Vieira de (2023)
Among the manufacturing processes for the production of microgeometries, micromachining offers the greatest flexibility, allowing the manufacture of parts with extremely small dimensions, in the micrometer range, with high precision and with a good surface finish. Micromachining is capable of processing several varieties of metals and their alloys, composites, polymers and ceramic materials. Despite many similarities, micromachining cannot be treated just as a simple reduction of the macro process, since the edge tool radius and the grain size of the machined material have a greater influence on the process. The main objective of this work is to determine the best cutting conditions, in terms of tool wear and part surface integrity, for micromilling of Inconel 718 nickel alloy. For this, microchannels were machined using end micromills of 400 μm in diameter, with two cutting edges, coated with TiAlN. The parameters of cutting speed (50.3 and 12.6 m/min), feed per tooth (5 and 10 µm/z) and cutting depth (10 and 40 µm) were varied. The machinability was investigated by analyzing the wear of the microtools, the behavior of the root mean square (Rq) roughness parameters of the surface of the microchannels and the burr formation. Wear was evaluated by comparing images obtained in the scanning electron microscope of used and new tools. It was found that the increase in cutting speed resulted in less wear when using a greater depth of cut, however, for a smaller depth, an inverse behavior was observed in wear. As for the quality of the machined surface, the results showed that the lowest roughness was found for the lowest cutting speed and depth. It was also observed that there was no significant difference in burr formation between the up-milling and down-milling and discordant sides and that there was greater burr formation when a greater cutting depth was used, with no significant change with the increase in cutting speed.